PENGUJIAN AKURASI BAKTERI E. coli DENGAN METODA MPN DAN PETRIFILM - Sri Unon Purwati; Efa Deswarni; Oktaria Diah Diah Pitalokasari (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2008)
The analytical of accuracy is important for quality control process in the laboratory. The analytical data accuracy for sampel Echerichia coli (E. coli) bacterya can be proceed by confirmation of reference E. coli positive culture. Test for accuracy covered morphology and physiological test. The morphology tests of E. coli bacteria resulted rod-shape, negative (-) for gram and no spore. The physiology test of E. coli bacteria gave positive characteristic for glucose fermentation (lactose, KIA), oxidize reaction (BGLB, EC, H2O2), H2S productivity reaction (SIM, KIA) and metabolite metallic form reaction from Lactose fermentation (EMB).